KERBAU MEDIA IN IMPROVING LEARNING RESULTS STUDENTS OF CLASS V SDN BANYUAJUH 4 - Cahyaning Setyatika Ramadhani; Evi Kharisma Azhari; Wahyu Kusuma Andini; Ananda Fitri Syarmila; Andika Adinanda Siswoyo (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Application of the Contextual Approach with the Buffalo Media (Kramangka Bangun Ruang) in Improving Learning for Grade V students at SDN Banyuajuh 04 academic year 2021/2022. The purpose of this study is to improve learning about the properties of prisms through the application of a contextual approach with buffalo media (framework) in fifth grade students of SDN Banyuajuh 04 Academic Year 2021/2022. This collaborative Classroom Action Research (CAR) was carried out in three cycles consisting of planning, implementation, observation and reflection. The subjects of this study were the fifth grade students of SDN Banyuajuh 04 for the academic year 2021/2022 with a total of 12 students. The conclusion of this study is that the application of a contextual approach with buffalo media can improve the learning of spatial construction in fifth grade students of SDN Banyuajuh 04 academic year 2021/2022.